Pengaruh Terapi Stretching Exercise terhadap Penurunan Skala Nyeri Sendi Lutut Pasien Osteoarthritis di Desa Ngemboh Kecamatan Ujungpangkah Kabupaten Gresik - Elfiani Suhar Lindah; Maulida Dwi Ayu Rachmawati; Ika Daimatur Rodhiyah; Virgianti Nur Faridah; Trijati Puspita Lestari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Osteoarthritis is often found in the elderly which is characterized by damage to the cartilage located in the joints caused by mechanical or biochemical stress on the body. Most osteoarthritis is found in the knee joint with complaints of pain and decreased range of motion. Its management can be carried out with non-pharmacological therapy, namely stretching exercise therapy. The purpose of this study was to determine the effect of stretching exercise therapy on decreasing the pain scale and increasing the range of motion of the knee joint in osteoarthritis patients. This study used a pre-experimental design with a one group pre-post test approach, a sample of 30 patients was obtained by total sampling technique. The instrument in this study was the verbal descriptor scale (VDS) pain scale observation sheet. Data analysis used the Wilcoxon signed rank test. The results of the study before stretching exercise therapy showed that the knee joint pain scale in osteoarthritis patients averaged 4.50 and after stretching exercise therapy the knee joint pain scale decreased to 1.93. And the Wilcoxon signed rank test obtained a significance value of p = 0.000 (p <0.05) which means that there is an effect of stretching exercise therapy on reducing the knee joint pain scale in osteoarthritis patients. Stretching exercise therapy is able to optimally increase muscle flexibility and range of joint motion so that it can have the effect of reducing or eliminating joint pain.